Pedobacter fastidiosus sp. nov., isolated from glacial habitats of maritime Antarctica. Issue 4 (20th April 2022) - Švec, Pavel; Králová, Stanislava; Staňková, Eva; Holochová, Pavla; Sedlář, Karel; Koudelková, Sylva; Krsek, Daniel; Grzesiak, Jakub; Šedo, Ondrej; Váczi, Peter; Urvashi,; Gupta, Vipin; et al.
Abstract : Strains P8930 T and 478 were isolated from Antarctic glaciers located on James Ross Island and King George Island, respectively. They comprised Gram-stain-negative short rod-shaped cells forming pink pigmented colonies and exhibited identical 16S rRNA gene sequences and highly similar MALDI TOF mass spectra, and hence were assigned as representatives of the same species. Phylogenetic analysis based on 16S rRNA gene sequences assigned both isolates to the genus Pedobacter and showed Pedobacter frigidisoli and Pedobacter terrae to be their closest phylogenetic neighbours, with 97.4 and 97.2 % 16S rRNA gene sequence similarities, respectively. These low similarity values were below the threshold similarity value of 98.7%, confirming the delineation of a new bacterial species. Further genomic characterization included whole-genome sequencing accompanied by average nucleotide identity (ANI) and digital DNA–DNA hybridization calculations, and characterization of the genome features. The ANI values between P8930 T and P. frigidisoli RP-3-11 T and P. terrae DSM 17933 T were 79.7 and 77.6 %, respectively, and the value between P. frigidisoli RP-3-11 T and P. terrae DSM 17933 T was 77.7 %, clearly demonstrating the phylogenetic distance and the novelty of strain P8930 T . Further characterization included analysis of cellular fatty acids, quinones and polar lipids, and comprehensive biotyping. All the obtained results proved the separation of strains P8930 T and 478 from the other validly named Pedobacter species, and confirmed that they represent a new species for which the name Pedobacter fastidiosus sp. nov. is proposed. The type strain is P8930 T (=CCM 8938 T =LMG 32098 T ).